PENGARUH MODEL GUIDED DISCOVERY TERHADAP HASIL BELAJAR IPA SISWA SEKOLAH DASAR - Anggi Rizaldi; Kartono Kartono; Siti Halidjah (Universitas Tanjungpura, 2020)
Abstract This research aims was to understand the effect of guided discovery learning model to student learning’s result in natural science . The method was used in this research was experimental method, with type nonequivalent control group design. Population in this research is all students grade III of elementary school 66 Pontianak City. Sample in this research were students of grade III B (31 students) and III A (32 students). Data collecting technique used was measurement technique while data collecting tool is the test. Based on the results of data analysis, average student learning result of the experimental class was 72,72 while the control class was 68,43. Result of hypothesis test (t-test) using t-test separated varians obtained thitung 2,31 and ttabel 1,67 (significant level (α) = 5% and dk = 61) that indicated thitung was bigger than ttabel, so hypothesis research accepted. In this research the effect size is 0,49 . It means that guided discovery learning model give effect to student learning result in natural science on grade III of elementary school 66 Pontianak City. Keyword: Effect, Guided Discovery, Learning Result.